Japán szerepe Közép-Európában, egy „feljövő" multipoláris világban - Berényi, Judit (Marketing & Menedzsment, 2019)
Traditionally, Japan has not enjoyed a significant presence in either Eastern Europe (the former Soviet Union west of the Urals), or in Central Europe. However, for a short time during the early Meiji period at the beginning of the 1880s, Japan looked to the Habsburg and Russian empires as appropriate development models1. Only in the latter part of the 19th century did Japan turn to the examples of Germany and England to adapt legal, military, and postal systems, and others, to the circumstances prevailing in Japan. In subsequent years, due to geographical distance, religious and cultural differences, and a general lack of mutual knowledge, there were to be very few ties between Japan and Central Europe. The Cold War era resulted in an artificial separation of the countries of the two blocs, with Japan and the Central European countries belonging to different alliances which had very low levels of political contact. The highly complex nature of Soviet-Japanese relations exercised a diversionary influence upon political relations, with economic relations mostly determined by political and security priorities. Indeed, both in Japan and Eastern Europe, a kind of inward looking economic autarky prevailed, although in the case of Japan this was tempered by a successful obsession with export-led growth.